Experimental investigation of bubble breakup in bubble chains rising in a liquid metal. (July 2019) - Keplinger, O.; Shevchenko, N.; Eckert, S.
Highlights: X-ray radiography combined with high-speed video imaging was used to visualize the bubble breakup in bubble chains rising in opaque liquid metals. The processes of bubble breakup were found to proceed in a qualitatively similar way as for the case of water or highly viscous fluids. The observations indicate that the turbulent flow in the immediate vicinity of the bubbles has an important influence on whether breakup occurs or not. Abstract: The process of bubble breakup in a liquid metal was studied by X-ray radiography and high-speed video imaging. Argon gas bubbles were injected through a single orifice at the bottom of a rectangular vessel filled with the eutectic GaInSn alloy. Moderate gas flow rates were applied at isothermal conditions resulting in the formation of bubble chains. The bubble breakup events observed in the chosen experimental geometry were mainly initiated by bubble collisions or by the effect of local shear flow. We present experimental results accompanied by statistical analysis of the bubble breakup frequency, number of daughter bubbles and their size distribution, bubble velocities before and after the breakup process for a broad range of Argon gas flow rates.